Identification of an optimal sampling position for stable isotopic analysis of bone collagen of extinct moa (Aves: Emeidae) - Holdaway, R.; Hawke, D.; Bunce, Michael; Allentoft, M. (Ornithological Society of New Zealand Inc., 2011)
Stable isotopic (d13C; d15N) analysis of bone collagen and other refractory biological materials is a mainstay of palaeoecological research, but comparability between individuals depends on homogeneity within the sample specimens. Long bones of extinct New Zealand moa display lines of arrested growth that reflect prolonged development over several years, leading to potential systematic inhomogeneity in stable isotopic enrichment within the bone. We tested whether the isotopic content within a Euryapteryx curtus tibiotarsus is homogeneous by measuring d15N and d13C values in 6 adjacent 1cm-diameter cortical bone cores arranged along the bone axis from each of the proximal and distal ends. We then measured isotopic ratios in 5 radial slices of a core from the mid-shaft of a Pachyornis elephantopus tibiotarsus to see if there was any depth (ontogenetic) effect at a single sampling point. The d13C value increased with distance from the proximal bone end, but neither d13C nor d15N values in samples from the distal end of the bone were correlated with position. Within mid---shaft cortical bone, the d13C value decreased with depth but d15N values were constant. Sampling the entire depth of cortical bone from the caudal surface at the distal end of the tibiotarsus, if feasible, therefore provides a spatially homogenous material, free of maturation effects on stable isotopic composition. If for any reason that position cannot be sampled, the outer (radial) layer at the mid-shaft can be substituted.